(untitled) - Bloom, Susan Ruddick (Amsterdam, 2006)
Using Painter and Photoshop, you'll discover ways to incorporate watercolors, pastels, oils, charcoals, and collage into your digital images. This book discusses at length the large varity of methods that can be used by you, the visual artist, to create fine art.
Keywords: Graphic arts,Photomontage,Computer graphics,Nghệ thuật đồ họa,Đồ họa máy tính; Computer programs,Máy tính